Chronic fatigue syndrome: a cognitive approach. - Surawy, C; Hackmann, A; Hawton, K; Sharpe, M (1995)
Observations concerning the characteristics of patients who presented to a medical clinic with a principal complaint of chronic medically unexplained fatigue (Chronic Fatigue Syndrome or CFS) are described, including the cognitions (thoughts and assumptions) elicited from a sample of these patients who were treated using cognitive behavioural therapy. On the basis of these observations a cognitive theory of the aetiology of CFS is proposed. These observations have implications for the treatment of patients with CFS.